What is the cost-effectiveness of menu calorie labelling on reducing obesity-associated cancer burdens? An economic evaluation of a federal policy intervention among 235 million adults in the USA. Issue 4 (18th April 2023) - Du, Mengxi; Griecci, Christina F; Cudhea, Frederick; Eom, Heesun; Wong, John B; Wilde, Parke; Kim, David D; Michaud, Dominique S; Wang, Y Claire; Mozaffarian, Dariush; Zhang, Fang Fang
Abstract : Objective: To assess the impact of menu calorie labelling on reducing obesity-associated cancer burdens in the USA. Design: Cost-effectiveness analysis using a Markov cohort state-transition model. Setting: Policy intervention. Participants: A modelled population of 235 million adults aged ≥20 years in 2015–2016. Interventions: The impact of menu calorie labelling on reducing 13 obesity-associated cancers among US adults over a lifetime was evaluated for: (1) effects on consumer behaviours; and (2) additional effects on industry reformulation. The model integrated nationally representative demographics, calorie intake from restaurants, cancer statistics and estimates on associations of policy with calorie intake, dietary change with body mass index (BMI) change, BMI with cancer rates, and policy and healthcare costs from published literature. Main outcome measures: Averted new cancer cases and cancer deaths and net costs (in 2015 US$) among the total population and demographic subgroups were determined. Incremental cost-effectiveness ratios from societal and healthcare perspectives were assessed and compared with the threshold of US$150 000 per quality-adjusted life year (QALY) gained. Probabilistic sensitivity analyses incorporated uncertainty in input parameters and generated 95% uncertainty intervals (UIs). Results: Considering consumer behaviour alone, this policy was associated with 28 000 (95% UI 16 300 to 39 100) new cancer cases and 16 700 (9610 to 23 600) cancer deaths averted, 111 000 (64 800 to 158 000) QALYs gained, and US$1480 (884 to 2080) million saved in cancer-related medical costs among US adults. The policy was associated with net cost savings of US$1460 (864 to 2060) million and US$1350 (486 to 2260) million from healthcare and societal perspectives, respectively. Additional industry reformulation would substantially increase policy impact. Greater health gains and cost savings were predicted among young adults, Hispanic and non-Hispanic Black individuals. Conclusions: Study findings suggest that menu calorie labelling is associated with lower obesity-related cancer burdens and reduced healthcare costs. Policymakers may prioritise nutrition policies for cancer prevention in the USA.